2018
DOI: 10.3802/jgo.2018.29.e55
|View full text |Cite
|
Sign up to set email alerts
|

Risks of cervical intraepithelial neoplasia grade 3 or invasive cancers in ASCUS women with different management: a population-based cohort study

Abstract: ObjectiveTo investigate the progression risk of atypical squamous cells of undetermined significance (ASCUS) with different clinical managements.MethodsWomen with their first diagnosis of ASCUS cytology were retrieved from the national cervical cancer screening database and linked to the national health insurance research database to identify the management of these women. The incidences of developing cervical intraepithelial neoplasia grade 3 and invasive cervical cancer (CIN3+) were calculated, and the hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Tai et al. reported that the incidence of CIN3+ lesions in the women aged over 60 years was higher than that in the women aged between 30 and 60 years ( Tai et al., 2018 ). Similar to other studies, the detection rate of CIN2+ in the post-menopausal women in this study was significantly lower than that in the pre-menopausal patients with ASC-US.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tai et al. reported that the incidence of CIN3+ lesions in the women aged over 60 years was higher than that in the women aged between 30 and 60 years ( Tai et al., 2018 ). Similar to other studies, the detection rate of CIN2+ in the post-menopausal women in this study was significantly lower than that in the pre-menopausal patients with ASC-US.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the detection rate of CIN2+ in women with ASC-US over 50 years of age is much higher than that under 50 years of age ( Wang et al., 2020b ). In one survey, the incidence of CIN3+ lesions was higher in women younger than 30 years and those older than 60 years old ( Tai et al., 2018 ). However, some studies have suggested that there is no difference in the HSIL+ detection rate in women with ASCUS before and after 50 years old ( Abdulaziz et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%